2022
DOI: 10.1177/17456916211029964
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health During the First Year of the COVID-19 Pandemic: A Review and Recommendations for Moving Forward

Abstract: COVID-19 has infected millions of people and upended the lives of most humans on the planet. Researchers from across the psychological sciences have sought to document and investigate the impact of COVID-19 in myriad ways, causing an explosion of research that is broad in scope, varied in methods, and challenging to consolidate. Because policy and practice aimed at helping people live healthier and happier lives requires insight from robust patterns of evidence, this article provides a rapid and thorough summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
350
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(388 citation statements)
references
References 141 publications
30
350
7
1
Order By: Relevance
“…Specifically, coronavirus-related PTSD, stress, and insufficient PA decreased between T1 and T2, while depression, anxiety, and suicidal/self-harm ideation remained unchanged on average. This pattern of results is partly concurrent with recently published studies that followed changes in mental health indicators over time during the pandemic [15,16]. However, our research was conducted between the second and third waves of the COVID-19 pandemic, whereas previous studies have reported mental health outcomes from the first wave.…”
Section: Mental Health Indicators Over Timesupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, coronavirus-related PTSD, stress, and insufficient PA decreased between T1 and T2, while depression, anxiety, and suicidal/self-harm ideation remained unchanged on average. This pattern of results is partly concurrent with recently published studies that followed changes in mental health indicators over time during the pandemic [15,16]. However, our research was conducted between the second and third waves of the COVID-19 pandemic, whereas previous studies have reported mental health outcomes from the first wave.…”
Section: Mental Health Indicators Over Timesupporting
confidence: 89%
“…A meta-analysis of 65 longitudinal cohort studies comparing mental health before versus during the COVID-19 pandemic reported a significant increase in both anxiety and depression during the outbreak of the pandemic (March-April 2020), followed by a decline to near pre-pandemic levels on most measures except depression by mid-2020 [15]. Similarly, a review conducted by Aknin and colleagues [16] on mental health during the first year of the COVID-19 pandemic found evidence that anxiety, depression, and distress increased in the early months of the pandemic, after which some studies reported a decline to pre-pandemic levels, while other studies reported persistently elevated levels of mental distress compared to pre-pandemic levels [16]. A longitudinal study conducted in Australia during the pandemic showed that the number of participants with clinical levels of depressive, anxiety, or insomnia symptoms did not differ statistically between April and September 2020, whereas well-being and stress showed a slight improvement [17].…”
Section: Introductionmentioning
confidence: 93%
“…By the fall of 2020, when we recruited our participants, nature exposure may have become less of a novelty, or may have perhaps become less appealing because of cooler temperatures. This is consistent with research suggesting that the well-being markers returned to pre-pandemic levels by the fall of 2020 [30]. Moreover, some studies indicate that the participants were not spending more time in nearby greenspaces [54,55].…”
Section: Discussionsupporting
confidence: 88%
“…For example, in November 2020, more Canadians reported having better mental health than earlier on in the pandemic, with similar levels to those reported in 2019 (pre-pandemic [31]). Life satisfaction seems to be relatively unchanged (in some people), according to both longitudinal and repeated cross-sectional research [30]. Thus, we expected that the pandemic might have impacted the students' subjective well-being and contacts with nature, but we viewed this study as largely exploratory.…”
Section: Current Studymentioning
confidence: 98%
See 1 more Smart Citation